Fiscal composition and aid effectiveness: A political-economy model - Paul Mosley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
In accounting for the rather gloomy trend of the aid effectiveness literature over the last few years, one explanatory strand has been fiscal, suggesting in particular that aid flows in weak states have tended to erode the taxbase and the structure of institutions. We pursue this idea, tracing the link from politics to domestic tax effort and then using the influence of this on expenditure to explain the leverage of aid. Thus, we argue that in the long run, tax effort determines the effectiveness of aid, and this relationship operates simultaneously in some countries with the negative link in the opposite direction, from aid to domestic tax effort, as observed by Bräutigam and Knack (2004) and others. We find that tax effort and the ability of the state to diversify its taxation structure are important determinants of long-term growth and aid effectiveness, and in our model, we find that overall aid effectiveness is, in a 3SLS model, weakly positive and significant, echoing the findings of Arndt, Jones and Tarp (2009) and Minoiu and Reddy (2010); however, these findings are not robust when retested using the GMMapproach favoured by the literature. A more robust finding, and a key message for policy, is that a broadening of the tax structure in low-income countries is crucial in order to enable those countries to escape from the 'weak state - 3; low tax trap', and to make aid more effective.
Keywords: O23; H20; 330; aid effectiveness; tax policy